PENINGKATAN DAYA TERIMA DAN KADAR PROTEIN NUGGET SUBSTITUSI IKAN LELE (CLARIAS BATRACHUS) DAN KACANG MERAH (VIGNA ANGULARIS) - S R Widya Areta Humaniora Justisia; Annis Catur Adi (Media Gizi Indonesia, 2016)
Catfi sh and red beans are high in protein and essential amino acid than can be processed into nuggets and used as high-protein snack alternative. This research aimed to determine the effect of catfi sh and red beans toward the acceptance and protein content, as well as determine the best composition to produce a good quality nuggets. Type of research in the development formula using true experimental with a completely randomized design. There were four (4) types of treatment (combination of catfi sh, catfi sh bones, and red beans) with three (3) times replication. Panelist used was 35 untrained panelists. Product acceptance was tested using statistical analysis Kruskal Wallis and Mann Whitney (ƒ¿ . 0.05). The result of organoleptic tests showed the most preferred nugget is F1 (combination of catfi sh and red beans). Highest increased protein per 100g nugget is F1 (combination of catfi sh and red beans) with 14.5 gcompare to F0 (catfi sh) with 11,5 g, there was signifi cant difference between F0 and F1, F2, F3, F4 to the characteristic of odour (p = 0.000), texture (p = 0.008), fl avor (p = 0.000), and form (p = 0.000). The best composition formula is F1 (combination of catfi sh and red beans).The best formula in terms of its composition, acceptability, and nutritionalvalue was F1 (combination of catfi sh and red beans).Keywords: acceptance, catfi sh, red beans, protein